Wanita dan Pendidikan: Sampai dimana Masih Ada Diskriminasi terhadap Wanita? - Sukanti Suryochondro (Antropologi Indonesia, 1992)
Legally there is no discrimination against women in the field of education, such as discernable in laws concerning formal education. Schools are generally co-educational; even those schools which initially are meant to enroll only boys (technical schools) or only girls (schools for home economic) are how open to both sexes. However statistical data show that there is a greater percentage of illiteracy among woman...[...]Non-formal education is provided by governmental instances, women's organization and private enterprises as well with a view to increasing the potentials of men and women; enrollment in these courses, arranging from literacy classes to agricultural training and in home economics, is voluntarily. Informal education is received through experiences in the family circle and other social groups, exposure to the mass media and by attending the traditional and modern theater. To what extent discrimination against women is apparent through informal education further social research may be able to reveal.